(untitled) (Proceedings of International Conference on Scientific Research in Natural and Social Sciences, 2024)
The purpose of study This is For know implementation of national programs empowerment public independent rural. The data collection tools used are divided into: observation, questionnaires , interviews and documentation . Analyze data with use analysis descriptive qualitative , which is later analyzed through data collection, distribution loaded frequency in form table. Research result show that implementation of national programs empowerment public independent rural can said its implementation No walk with Good . This result get it of the total sub variables added up Where after added up to the total score his presentation reached 86.56%.